Shorten tables of estimated mortality for Cienfuegos province in 2014-2016 and 2017-2019 - Yenisvel Yut Vidal; Alfonso Farnós Morejón (Medisur)
Background: the calculation of life expectancy at birth and at different ages acquires certain relevance in socio-demographic contexts such as the Cuban one, where the lengthening of survival is one of the fundamental characteristics of demographic dynamics. Objective: to present shorten tables of estimated mortality for the Cienfuegos province. Methods: retrospective descriptive study, which had as its universe the Cienfuegos entire average population in 2015 and 2018, as well as the deaths that occurred from 2014 to 2019. The analyzed variables were: mortality (life expectancy) and rate of Child mortality. The data was obtained from the interfaces and statistical yearbooks of the National Office of Statistics and Information. Results: it was estimated that life expectancy at birth 2014-2016 and 2017-2019, regardless of sex, exceeded 76 years, with 76.50 and 76.32 years respectively for men; and 81.66 and 81.15 years for women. Infant mortality ranged between 1.78 and 4.59 deaths per thousand live births. Conclusion: according to the demographic procedure used, the survival capacity of women from Cienfuegos tends to increase in relation to the period 2011-2013, while men experience a decrease in this, which shows a slight increase in the female advantage of differential of survival life expectancy at birth relative to men.